STRATEGI ROOM ATTENDANT DALAM MENINGKATKAN KUALITAS PELAYANAN TERHADAP TAMU DI HYATT REGENCY YOGYAKARTA - , VINSENSIUS TRIYAN AMSIT HULU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the final project, entitled The Strategy of Room Attendant in Improving of Service Quality to Guests at Hyatt Regency Yogyakarta aims to find out the strategy of room attendant in the process of completing the work to be completed on time and to get optimal results. In addition, to find out the strategy of laundry division providing linnen in a timely manner for the room attendant to support the process of cleaning guest rooms. To obtain the results of this research, the author go into the field to do work practices directly at Hyatt Regency Yogyakarta Hotel. Then the authors make an interview to some housekeeping department staff, including supervisors and housekeeping manager that was related to the authorâs purpose in this research. The author also took some photo documentation at the research site. The results of the research that has been done is to clean a guest room are necessary steps in the correct order so that the work can be completed properly and can save time. It also requires great care of the laundry attendant sorting out the dirty linnen that linnen stains or spots can be identified and cleaned up immediately. So that it does not increase the working time to replace the linnen room attendant in the guest rooms.